Hungarian Monitoring, 28 November 1988 . [Magyar rádiófigyelő], 1988. november 28 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - On today's session of the CPSU Central Committee - Polish trade unions prepare for Wednesday's television debate - Satrov's article in Izvestiya on events in Azerbaijan - Ceauşescu's position on establishment of unified Romanian national state Domestic Affairs: - Draft modifications to the election law - Meeting between government and National Council of Trade Unions (SZOT) representatives - Péter Várkonyi's Malaysian visit - Romanian refugees - Football match-fixing affair Economy: - Shortage of capital needs to be alleviated for joint companies: planned easing of authorizations required for company formation - Agricultural cooperatives aggrieved that trade banks retroactively raised cooperative loan interest rates - “Hungarian Economy Days” begins in Israel, minister for industry and trade A. Sharon gives opening address Külpolitika: - A SZU KB-nak mai üléséről - A lengyel szakszervezetek készülnek a szerdai tv-vitára - Satrov írása az azerbajdzsáni eseményekkel kapcsolatban az Izvesztyijában - Ceauşescu álláspontja az egységes román nemzeti állam létrejöttéről Belpolitika: - A választójogi törvény módosítás tervezete - A kormány és a SZOT képviselőinek találkozója - Várkonyi Péter malajziai látogatása - A romániai menekültek ügye - Bunda - Ügy Gazdaság: - Tőkeszegénységünk enyhítésére szükség van a vegyes vállalatokra. A megalakulás engedélyezésének könnyítését tervezik - A tsz-ek sérelmezik, hogy a kereskedelmi bankok visszamenőleg felemelték a szövetkezeti hitelek kamatait - Magyar Gazdasági Napok kezdődtek Izraelben. A megnyitón beszédet mondott A. Saron ipari-kereskedelmi miniszter